Hunter S. Thompson : fear, loathing, and the birth of Gonzo - McEneaney, Kevin T. (Rowman & Littlefield, 2016)
"A decade after Hunter S. Thompson's death, his books--including Hell's Angels, The Curse of Lono, The Great Shark Hunt, and Rum Diary--continue to sell thousands of copies each year, and previously unpublished manuscripts of his still surface for publication. While Thompson never claimed to be a great writer, he did invent a new literary style--'gonzo'--that has been widely influential on both literature and journalism. Though Thompson and his work engendered a significant--even rabid--following, relatively little analysis has been published about his writing. In Hunter S. Thompson: Fear, Loathing, and the Birth of Gonzo, Kevin T. McEneaney examines the intellectual background of this American original, providing biographical details and placing Thompson within a larger social and historical context. A significant portion of this book is devoted to the creation, reception, and legacy of his most important works, particularly Fear and Loathing in Las Vegas. In addition to discussing influences on Thompson's work--including Homer, Nietzsche, Spengler, Melville, Twain, Hemingway, Fitzgerald, Kerouac, and others--as well as the writers Thompson influenced, McEneaney also explains the literary origins of gonzo. With new biographical information about Thompson and an examination of his writing techniques, this book provides readers with a better understanding of the journalist and novelist. A look beyond the larger-than-life public persona, Hunter S. Thompson: Fear, Loathing, and the Birth of Gonzo will be of great interest to fans of Thompson's work as well as to those wanting to know more about gonzo journalism and literature"--Provided by publisher